Efficacy of phytoextracts, essential oils, homeopathic drugs, organic amendments and fungicides for the management of pigeonpea wilt - Kumar, Sunil; Upadhyay, J P (Indian Journal of Plant Protection, 2020)
Phytoextract, essential oils, homeopathic drugs, organic amendment and fungicides were evaluated in vitro as well as in vivo against Fusarium udum the causal agent of pigeonpea wilt. Among the phytoextract, maximum radial growth inhibition (71.0%) of F. udum was recorded with Allium sativum at 10 % concontration after 120 hrs in vitro and maximum disease control (31.6%) in seed treatment. The oils of Eucalyptus citridora and Cymbopogon flexuosus showed inhibition zone and inhibited the growth of F. udum by 15.6 and 11.6 % after 120 hrs of incubation, respectively whereas maximum disease control (33.2%) was recorded with E. citridora oil seed treatment. Acid nitric 30 potency at 500 µg/ml concentrations inhibited 64.6% mycelial growth of F. udum and recorded maximum disease control (35.5 %). The growth inhibition of F. udum with different organic amendments ranged from 1.06 to 5.51 per cent after 120 hrs of incubation. Mustard cake was found to slightly promote (-1.26%) the growth of F. udum. Soil application of Karanj cake resulted in 40.3% disease control followed by vermicompost 33.22 %. Among the fungicide, carbendazim, carbendazim + mancozeb and carboxin + thiram completely (100%) inhibited the radial growth of F. udum at 1000 µg/ml and minimum wilt incidence (27.08%) and maximum disease control was recorded in seed treatment with carbendazim.